h - Foresti, Sara.; Yung, Moti.; Martinelli, Fabio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 17th European Symposium on Computer Security, ESORICS 2012, held in Pisa, Italy, in September 2012. The 50 papers included in the book were carefully reviewed and selected from 248 papers. The articles are organized in topical sections on security and data protection in real systems; formal models for cryptography and access control; security and privacy in mobile and wireless networks; counteracting man-in-the-middle attacks; network security; users privacy and anonymity; location privacy; voting protocols and anonymous communication; private computation in cloud systems; formal security models; identity based encryption and group signature; authentication; encryption key and password security; malware and phishing; and software security.
A Particle Swarm Embedding Algorithm for Nonlinear Dimensionality -- ABC-Miner: An Ant-Based Bayesian Classification Algorithm -- Analysing Robot Swarm Decision-Making with Bio-PEPA -- Automatic Generation of Multi-objective ACO Algorithms for the Bi-objective Knapsack -- Bare Bones Particle Swarms with Jumps -- Hybrid Algorithms for the Minimum-Weight Rooted Arborescence Problem -- Improving the cAnt-MinerPB Classification Algorithm -- Introducing Novelty Search in Evolutionary Swarm Robotics -- Measuring Diversity in the Cooperative Particle Swarm Optimizer -- Multi-armed Bandit Formulation of the Task Partitioning Problem in Swarm Robotics -- Scalability Study of Particle Swarm Optimizers in Dynamic Environments -- Self-reconfigurable Modular e-pucks -- Task Partitioning via Ant Colony Optimization for Distributed Assembly -- The Self-adaptive Comprehensive Learning Particle Swarm Optimizer -- Towards Swarm Calculus: Universal Properties of Swarm Performance and Collective Decisions -- A Hybrid Particle Swarm Optimization Algorithm for the Open Vehicle Routing Problem -- A Self-adaptive Heterogeneous PSO Inspired by Ants -- A(3z(BThermodynamic(3y(BApproach to Multi-robot Cooperative Localization with Noisy Sensors -- AcoSeeD: An Ant Colony Optimization for Finding Optimal Spaced Seeds in Biological Sequence Search -- Analysis of Ant-Based Routing with Wireless Medium Access Control -- Ant-Based Approaches for Solving Autocorrelation Problems -- Collision-Induced (3z(BPriority Rule(3y (BGoverns Efficiency of Pheromone-Communicating Swarm Robots -- Dynamic Load Balancing Inspired by Cemetery Formation in Ant Colonies -- Feasibility of an Ant Colony Optimization Algorithm for Multi-leaf Collimator (MLC) Aperture Definition and Beam Weighting in Volumetric Modulated Arc Therapy (VMAT) Radiotherapy Treatment Planning -- Ant Swarm Foraging from Physical to Virtual and Back Again -- Improving Peer Review with ACORN: ACO Algorithm for Reviewer$1 (Bs Network -- Learning Finite-State Machines with Ant Colony Optimization -- Mobbing Behavior and Deceit and Its Role in Bio-inspired Autonomous Robotic Agents -- Performance of Bacterial Foraging Optimization in Dynamic Environments -- Piecewise Linear Approximation of n-Dimensional Parametric Curves Using Particle Swarms -- Probabilistic Stochastic Diffusion Search -- Self-organized Clustering of Square Objects by Multiple Robots -- Self-reproduction versus Transition Rules in Ant Colonies for Medical Volume Segmentation -- Swarm Interpolation Using an Approximate Chebyshev Distribution -- Using MOPSO to Solve Multiobjective Bilevel Linear Problems -- Clustering Moodle Data via Ant Colony Optimization -- Continuous Trait-Based Particle Swarm Optimisation (CTB-PSO) -- Exploring Different Functions for Heuristics, Discretization, and Rule Quality Evaluation in Ant-Miner -- Fuzzy-Based Aggregation with a Mobile Robot Swarm -- Maturity of the Particle Swarm as a Metric for Measuring the Particle Swarm Intelligence -- Multi-objective Firefly Algorithm for Energy Optimization in Grid Environments -- Particle Swarm Optimization with Random Sampling in Variable Neighbourhoods for Solving Global Minimization Problems.s
Keywords: Computer science; Software engineering; Data protection; Data encryption (Computer science).; Information Systems; Computer Science; Systems and Data Security; Data Encryption; e-Commerce/e-business.; Management of Computing and Information Systems; Software Engineering; Information Systems Applications (incl. Internet).